2022
DOI: 10.3390/ani12162045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Ramie Powder at Various Levels on the Growth Performance, Meat Quality, Serum Biochemical Indices and Antioxidative Capacity of Yanling White Geese

Abstract: To investigate the effects of different levels of ramie powder (Boehmeria nivea (L.) Gaudich.) (i.e., 0%, 6%, 12% and 24%) on the production performance, serum biochemical indices, antioxidative capacity and intestinal development of Yanling white geese, a total of 256 geese at 56 days of age were randomly divided into four groups and fed a control diet and the control diet supplemented with 6%, 12% and 24% ramie powder, respectively, for 42 days. The results show that dietary supplementation with 12% ramie po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…CTX is capable of causing oxidative stress in the body, after oxidative stress, the antioxidant defense system of the body is disrupted ( Has et al, 2019 ; Zhu et al, 2022 ). Exogenous dietary additives and ingredients may affect growth performance and antioxidation in animals ( Ma et al, 2021 ; Chen JY et al, 2022 ; Chen FM et al, 2022 ). It has been demonstrated that Amaranthus polysaccharides can alleviate CTX-induced oxidative stress in mice ( Niu et al, 2020 ) and enhance the antioxidant enzyme activities of mice in an immunosuppressed state.…”
Section: Discussionmentioning
confidence: 99%
“…CTX is capable of causing oxidative stress in the body, after oxidative stress, the antioxidant defense system of the body is disrupted ( Has et al, 2019 ; Zhu et al, 2022 ). Exogenous dietary additives and ingredients may affect growth performance and antioxidation in animals ( Ma et al, 2021 ; Chen JY et al, 2022 ; Chen FM et al, 2022 ). It has been demonstrated that Amaranthus polysaccharides can alleviate CTX-induced oxidative stress in mice ( Niu et al, 2020 ) and enhance the antioxidant enzyme activities of mice in an immunosuppressed state.…”
Section: Discussionmentioning
confidence: 99%
“…The diet's formulation and composition can potentially impact the growth performance and antioxidant capacity of animals, as stated in references [26][27][28]. Zhang et al showed that SARA elevated systematic oxidative status and enhanced autophagy in the liver, and suppressed SIRT1 and FOXA2 may mediate enhanced oxidative damage and autophagy in the livers of dairy cows fed a HC diet [29].…”
Section: Discussionmentioning
confidence: 99%
“…is a perennial bast fiber plant cultivated widely in southeastern Asia and the Pacific Rim, including China and India. Ramie is rich in protein and has higher biomass, making it a significant source of forage and quality fiber for textile industries [1]. The low germination rates and survival of conventional ramie seed propagation make vegetative propagation, such as hydroponic technology, the best option for large-scale production [2].…”
Section: Introductionmentioning
confidence: 99%